The development of museum movement in the Prikarpation for the year 1991-2014: source aspects - Igor Daniluk (Cхід, 2018)
The article reveals the main aspects of the development of museums in the Ivano-Frankivsk region in the sources. Characterizes the specifics of the formation of funds and the receipt of exhibits in the museum. The necessity of distribution and creation of museum institutions which are not only of a social importance, but also educational for students and students in legislative documents, decrees and sources is analyzed. The main archival files of Ivano-Frankivsk regional archives are described, which describe the activity of museums in the specified historical interval.